China's Road to Greater Financial Stability : Some Policy Perspectives - Das, Udaibir (International Monetary Fund, 2013)
China has reached a stage where further financial sector reforms appear essential. As the reform process progresses and macrofinancial linkages deepen, the preservation of financial stability will become a major policy preoccupation. This publication draws upon contributions from senior Chinese authorities and academics as well as staff from the IMF to discuss the financial policy context within China, macroeconomic factors affecting financial stability, and the critical role of financial system oversight. It seeks to improve the understanding of the financial sector policy processes underway and the shifts taking place among China's economic priorities.